Education Dualism and Secularism: An Integrated Education Approach to the Education System in Uganda - Matovu, Musa (EDUCARE, 2013)
ABSTRACT: Dualism in education is not good for Muslim education and an integrated curriculum should be opted in order to resist secularism in Muslim communities. The purpose of this paper was to underscore the rapid spread of secularism and the acceptance of education dualism in the Muslim education in Uganda. This paper gives a detailed explanation of education dualism and secularism in Muslim communities, most especially in Uganda. The paper also discloses that integration of the curriculum (âmodernâ and religious knowledge) is overdue to improve on the Muslim education in the country. With the use of document analysis method, this paper explicates secularism and education dualism, and also mentions on how they have penetrated and been accepted by the Ugandan Muslims community without scrutiny. This paper discloses the challenges of education dualism and secularism in the Muslim education which have led to Muslimsâ intellectual, cultural, and social divergences from Al-Qurâan and Al-Sunnah in their education systems and practices. Also the paper proposes the possible solutions on how to exterminate education dualism and secularism from the Muslim education and communities in Uganda. In general, the scene of explanation of secularism and education dualism in Muslim communities in this paper was based on the Ugandan experiences.KEY WORDS: Education dualism, secularism, integration, Ugandan Muslims community, and challenges and solutions.About the Author: Musa Matovu is a Ph.D. Candidate at the Institute of Education IIUM (International Islamic University of Malaysia), Gombak Campus, P.O. Box 10, 50728 Kuala Lumpur, Malaysia; and also a Lecturer at the Faculty of Education IU (Islamic University) in Uganda. He can be contacted via his e-mail address at: matovumousa@yahoo.comHow to cite this article? Matovu, Musa. (2013). âEducation Dualism and Secularism: An Integrated Education Approach to the Education System in Ugandaâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.117-132. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 17, 2012); Revised (January 20, 2013); and Published (February 17, 2013). Â Â